Analiza technik reprezentacji wymagań stosowanych w procesie budowy systemów informatycznych - Sobczak, Andrzej (Analysis of the Techniques to Represent Requirements in the Process of Building Information Systems, 2005)
Representation of the requirements acquired from the requirements stakeholders in particular, constitute critical factors affecting the success of developing information systems. Such representation should constitute a coherent set in spite that it is usually received from very different professional groups, of widely varying competences, participating in the implementation of a specific project. This is made difficult by the fact that the requirements collected from the main stakeholders are imprecise and very weakly structured. The article comprises review of techniques to represent the requirements in the process of building information systems. The research shall focus on new techniques for requirements representation - using knowledge engineering (especially using ontology). This is associated with the fact that an approach is becoming more and more popular according to which "the most essential thing is the knowledge held by people and organisations, and the knowledge should be articulated and formalised before attempting to build" an information system.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 296-304